2015
DOI: 10.1371/journal.pone.0127549
|View full text |Cite
|
Sign up to set email alerts
|

A DJ-1 Based Peptide Attenuates Dopaminergic Degeneration in Mice Models of Parkinson's Disease via Enhancing Nrf2

Abstract: Drugs currently used for treating Parkinson's disease patients provide symptomatic relief without altering the neurodegenerative process. Our aim was to examine the possibility of using DJ-1 (PARK7), as a novel therapeutic target for Parkinson's disease. We designed a short peptide, named ND-13. This peptide consists of a 13 amino acids segment of the DJ-1-protein attached to 7 amino acids derived from TAT, a cell penetrating protein. We examined the effects of ND-13 using in vitro and in vivo experimental mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Recently, a short, cell penetrating, peptide derivative of DJ-1 was shown to attenuate H2O2, 6-OHDA, and DA induced oxidative stress in neuroblastoma cell lines (Lev, Barhum et al 2015).…”
Section: Nrf2 and Park Gene Productsmentioning
confidence: 99%
“…Recently, a short, cell penetrating, peptide derivative of DJ-1 was shown to attenuate H2O2, 6-OHDA, and DA induced oxidative stress in neuroblastoma cell lines (Lev, Barhum et al 2015).…”
Section: Nrf2 and Park Gene Productsmentioning
confidence: 99%
“…Dr. Daniel Offen’s laboratory, at the University of Tel Aviv, developed a 13 aa-long peptide derived from the most conserved sequence of DJ-1 [ 23 ]. To achieve cell permeability, this 13 aa chain was fused to a 7 aa TAT sequence (YGRKKRR).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve cell permeability, this 13 aa chain was fused to a 7 aa TAT sequence (YGRKKRR). The resulting 20 amino acid compound was named ND-13 and was demonstrated to be effective in protecting neuronal cultures from the effects of relevant neurotoxins in the setting of Parkinson’s disease, amyotrophic lateral sclerosis or multiple system atrophy [ 23 , 24 , 25 ]. ND-13 exerts these protective effects by reducing apoptosis and by inactivating the proapoptotic protein caspase-3 in neuronal cell lines exposed to these neurotoxic insults.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from the Offen laboratory have shown that peptides derived from DJ‐1 is capable of cytoprotection. In these studies, a short DJ‐1‐based peptide named ND‐13 has been shown to protect cell death induced by oxidative stress from 3‐nitropropionic acid, hydrogen peroxide, 6‐OHDA, or DA treatment (Lev et al a; Glat, Ben‐Zur, Barhum, & Offen, ). This ND‐13 peptide also rescued NSC‐34 neuronal cells from peroxynitrite ion generator 3‐morpholinosydnonimine (SIN‐1)‐induced neurotoxicity (Lev, Barhum, Lotan, Steiner, & Offen, b).…”
mentioning
confidence: 99%